Contractual regulations on continuing vocational education and training in Germany - Sadowski, Dieter [Herausgeber]; Decker, Stefanie [Herausgeber] (Nomos Verl.-Ges., 1993)
"The reports shows how far social actors in Germany have moved towards agreements on further training for employees. The report is also concerned with how the experts, from collective bargaining parties and from management in a selected group of businesses, view these regulations, and whether they see a need for further collective regulations. One chapter is given over to the German system of training and the role of the State, with special reference to the self-regulating Federal Labour Office and its activities in the context of the Employment Promotion Act, as well as the chambers of commerce. The volume also contains a bibliography of the relevant literature." (author's abstract, IAB-Doku) ((en)) Der Bericht bildet einen Teil eines Projekts im Auftrag des FORCE- Programms "Further Training in Europe" der EG-Kommission. Er befasst sich mit vertraglichen Regelungen der Sozialpartner für die Weiterbildung von Arbeitnehmern. Ausserdem werden staatliche Regelungen (Arbeitsförderungsgesetz), Regelungen auf regionaler Ebene (Industrie- und Handelskammern, Teilnehmer an AFG- geförderten Massnahmen, Volkshoschulen und andere Einrichtungen), auf Wirtschaftszweigebene, auf betrieblicher Ebene (Feldstudien) beschrieben und analysiert. (IAB)
Keywords: S System beruflicher Bildung; S 1.3 Berufliche Erstausbildung; S 2.1.6 Arbeits- & Tarifrecht; T 4.6 Wirtschafts- und Rechtswissenschaften; S 3.5.4 Sozialpartner; S 3.2 Unternehmen und Behörden; Berufliche Weiterbildung; Recht; Berufsbildungssystem; Arbeitsförderungsgesetz (AFG); Tarifpolitik; Sozialpartner; Betrieb; Wirtschaftszweig; Tarifvertrag; Arbeitsbeziehungen; Quantitative Angaben